Multispecies foraminiferal geochemical compositions generated from IODP Site 359-U1467 - Stephanie Stainbank; Silvia Spezzaferri; Andres Rüggeberg; Jacek Raddatz; Erica S de Leau; Siyao M Yu; Manlin Zhang; Dick Kroon (PANGAEA, 2021)
The present datasets include multispecies foraminiferal geochemical data (δ^1?O, δ^1^3C, Mg/Ca), which was used to make seawater temperature and δ^1?O sw reconstructions for the Maldives Inner Sea across the Marine Isotope Stages (MISs) 1-2 and 10-13. All data comes from International Ocean Discovery Program (IODP) Site 359-U1467 samples. All data, other less otherwise indicated in the tables below, is new data generated in this study.